Development strategies for the rubberwood processing industries - Hock O S (In: Proceedings of the 2nd Rubberwood Seminar, 19-20 November 1985, Forest Research Institute of Malaysia, Kuala Lumpur, Malaysia, pp.72-93., 1985)
The paper estimates the availability of rubberwood for sawn timber conversion in the range of 1 to 2.9 million cu metres for the period 1985 to 2000. It is estimated that after taking into consideration current utilization, about 1 million cu metres of logs of diameter 15 cm and above are available for exploitation. The paper summarizes the current problems faced by the industry and propose the concept of an integrated rubberwood processing approach. The model for this concept which could include combinations of various manufacturing units is outlined together with economic analysis of its feasibility. The benefits to the small-holders and the national economy are outlined. It is envisaged that at least 10 of these models can be set up.
Keywords: Rubberwood industry; Rubberwood processing